Cytotoxic and genotoxic potential of respirable fraction of composite dust on human bronchial cells. Issue 2 (February 2020) - Cokic, Stevan M.; Ghosh, Manosij; Hoet, Peter; Godderis, Lode; Van Meerbeek, Bart; Van Landuyt, Kirsten L.
Highlights: A novel approach for collection of respirable fraction of composite dust. Respirable fraction of composite dust can induce both cytotoxic and mild genotoxic effect in 16HBE cells. Initial DNA damage and impairment of normal cell cycle is observable in subtoxic concentrations. Respirable particles of all tested composites were taken by the cells. Abstract: Objective: To determine the cytotoxic and genotoxic potential of the respirable fraction of composite dust (<4 μm) on human bronchial epithelial cells. Methods: Composite sticks of three commercial dental composites (Filtek Supreme XTE, Grandio, Transbond XT) were ground in an enclosed plexiglass chamber with a rough dental bur (grain-size 100 μm) and the generated airborne respirable dust was collected in a personal cyclone on a teflon filter (pore size 5 μm). Immediately after particle collection, the dust was quantified gravimetrically and the particles were suspended in cell culturing medium. Next, human bronchial epithelial cells (16HBE14o-) were exposed to the suspensions (3 μg/ml–400 μg/ml). After 24 h, cell viability (WST-1 assay) and membrane integrity (LDH assay) were evaluated. Furthermore, the genotoxic effect of a sub-cytotoxic concentration (50 μg/ml) of composite dust was evaluated by the comet assay after 3 h exposure and cell cycle disturbances were analyzed by flow cytometry. Cellular uptake of particles was evaluated by transmission electronic microscope (TEM). Results: For all three tested composite materials, a decrease in metabolic activity of 10–35% was observed when the cells were exposed to the highest concentrations (100 μg/ml–400 μg/ml). Toxicity was partially linked to membrane disruption especially after 72 h exposure. All tested composites provoked a mild genotoxic effect after short-term exposure compared to the control groups. TEM revealed that respirable particles of all tested composites were taken up by the cells. Significance: The respirable fraction of composite dust only showed cytotoxic effects at the highest concentrations, whereas mild genotoxicity was observed after exposure to a sub-cytotoxic concentration.